Pengaruh Profitabilitas, Lukuiditas, Leverage, Ukuran Perusahaan, Dan Kepemilikan Manajerial Terhadap Financial Distress Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Setiowati, Eni; Merawati, Luh Komang; Dicriyani, Ni Luh Gede Mahayu (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Cenderawasih, 2024)
If a company is unable to face competition between companies, the company could experience losses and ultimately cause the company to experience financial distress. Financial distress is defined as the stage of decline in a company's financial condition that occurs before bankruptcy or liquidation occurs. This research aims to determine the effect of profitability, liquidity, leverage, company size and managerial ownership on financial distress. This research analyzes manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this research are all manufacturing companies listed on the Indonesian Stock Exchange. The data used is secondary data from the company's annual financial reports. The research sample used purposive sampling. The final sample obtained was 74 companies. The analysis technique used is logistic regression analysis using the SPSS 25.0 program. The research results show that profitability has a negative effect on financial distress conditions and leverage has a positive effect on financial distress, while liquidity, company size and managerial ownership have no effect on financial distress.